2023
DOI: 10.1039/d3qo00403a
|View full text |Cite
|
Sign up to set email alerts
|

Expedient assembly of densely functionalized indanonesvianickel-catalyzed alkene hydroacylation with methyl esters

Abstract: Given the chemical feedstock availability but intrinsic chemical inertness, the development of applicable cross-couplings with methyl esters as acyl electrophiles remains highly desirable and particularly challenging. Herein, we report a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…These results showed that different position of substituent group had some effect on the reaction. It was worth noting that the compound 3 ha could be conveniently converted into 2-(4trifluoromethylphenyl)-3-indazolone (5 aa) [13] (Scheme 2), which was an investigational TRPV1 receptor antagonist for analgesics. [14] The yields of the products were decreased with increasing the steric hindrance of substituent.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results showed that different position of substituent group had some effect on the reaction. It was worth noting that the compound 3 ha could be conveniently converted into 2-(4trifluoromethylphenyl)-3-indazolone (5 aa) [13] (Scheme 2), which was an investigational TRPV1 receptor antagonist for analgesics. [14] The yields of the products were decreased with increasing the steric hindrance of substituent.…”
Section: Resultsmentioning
confidence: 99%
“…[12] A method was developed to synthesize 2-azobenzonitrile motif via electrochemically-driven azidation reactions of 2H-indazoles with manganese as the catalyst (Scheme 1c). [13] Based on these efforts, we herein report an electrochemical method for ringopening reaction of 2H-indazoles with alcohols to synthesize ortho-alkoxycarbonylated azobenzene under metal-free reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…They have found application in diverse therapeutic areas, including anti-inflammatory agents, anti-hyperlipidemia agents, anti-tumor agents, anti-diabetic agents, and Transient Receptor Potential cation subfamily V member 1 (TRPV1) receptor antagonists [ 6 , 7 , 8 , 9 , 10 ]. The significance of indazol-3-ones as pharmacophores has heightened interest in the development of practical and convenient synthetic methods for generating N -substituted indazol-3-one derivatives [ 11 , 12 , 13 , 14 , 15 ], which is crucial because the introduction of different substituents at the N -position can significantly affect their biological properties. Therefore, the existence of efficient synthetic methods to prepare N -substituted indazol-3-ones is crucial in the discovery of new drug candidates.…”
Section: Introductionmentioning
confidence: 99%
“…receptor antagonists [6][7][8][9][10]. The significance of indazol-3-ones as pharmacophores has heightened interest in the development of practical and convenient synthetic methods for generating N-substituted indazol-3-one derivatives [11][12][13][14][15], which is crucial because the introduction of different substituents at the N-position can significantly affect their biological properties. Therefore, the existence of efficient synthetic methods to prepare Nsubstituted indazol-3-ones is crucial in the discovery of new drug candidates.…”
Section: Introductionmentioning
confidence: 99%
“…As a privileged structural motif, indanone represents an important class of heterocycle compounds that have been discovered in synthetic chemistry, biology, pharmacology, and materials chemistry . In recent years, the indanone skeleton has garnered increasing attention from researchers . Therefore, it is of considerable significance to develop efficient and simple methods for synthesizing indanone compounds.…”
mentioning
confidence: 99%